2005
DOI: 10.1073/pnas.0409228102
|View full text |Cite
|
Sign up to set email alerts
|

Differences in color vision make passerines less conspicuous in the eyes of their predators

Abstract: Sexual selection often favors brighter and exaggerated traits, which also increase the risk of detection by predators. Signals that are preferentially conspicuous to conspecifics would reduce the predation cost of signaling and, therefore, might facilitate the evolution of stronger sexual and social signals. This selective signaling is possible if predators and prey have differently tuned sensory systems. By using a retinal model to compare reflectance from the plumages of Swedish songbirds to the reflectance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(166 citation statements)
references
References 39 publications
8
155
1
1
Order By: Relevance
“…Recent research concluded that avian plumage signals can exploit intertaxon perceptual differences (36), and inclusion of conspecific signals hidden from human investigators but shown in this study to be available to birds could further facilitate understanding of functions of plumage coloration. For example, since the discovery of sexual differences in the blue-UV crown coloration of blue tits (11)(12), color in this feather patch has been shown to be important in social interactions (37), mate choice (38), parental care (39), and offspring sex ratios (40).…”
Section: Resultsmentioning
confidence: 81%
“…Recent research concluded that avian plumage signals can exploit intertaxon perceptual differences (36), and inclusion of conspecific signals hidden from human investigators but shown in this study to be available to birds could further facilitate understanding of functions of plumage coloration. For example, since the discovery of sexual differences in the blue-UV crown coloration of blue tits (11)(12), color in this feather patch has been shown to be important in social interactions (37), mate choice (38), parental care (39), and offspring sex ratios (40).…”
Section: Resultsmentioning
confidence: 81%
“…Accordingly, Håstad et al (2005) showed that passerines exploited the differences in vision between them and their predators to avoid the exploitation of their visual cues. Both avoidance of exploitation and compensation behaviors may have masked the relationship between conspicuousness and mortality in some species, and they could explain some of the results reporting no such relationship (e.g., Huhta et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The model has been demonstrated to precisely describe visual discrimination in birds Goldsmith & Butler 2005) and has recently been successfully incorporated in the studies of perception of visual signals (e.g. Siddiqi et al 2004;Håstad et al 2005;Doucet et al 2007; Gó mez & Théry 2007;Avilés et al 2008). The model establishes a colour distance DS that describes the colour contrasts between two eggs as follows: where Df i is the log ratio of the quantum catches for cone i, for egg H and C.…”
Section: Methodsmentioning
confidence: 99%
“…Håstad et al 2005;Gó mez & Théry 2007;Avilés et al 2008). Further, following Håstad et al (2005) for the noise calculations, I used cone proportions of 1, 1.92, 2.68 and 2.7 for a UVS species , and assumed that the signalling noise for each cone was independent of light intensity.…”
Section: Methodsmentioning
confidence: 99%